1991
DOI: 10.1063/1.349531
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of CuAlSe2 grown by iodine chemical vapor transport

Abstract: Resistivities, carrier concentrations, optical absorption, and photoluminescences of undoped and Cd,Zn-doped CuAlSe2 single crystals grown by chemical vapor transport were studied. The electrical and optical properties were almost unchanged after annealing under Se pressure. However, the resistivity increased about seven orders of magnitude after annealing in vacuum. The resistivity also increased by Cd or Zn doping. The samples showed p-type conduction even when Cd or Zn was doped. An acceptor ionization ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…This is coincided with the mobility result obtained by Chichibu et al [18]. For the CuAlSe 2 bulk grown by iodine chemical vapor transport, they reported that the mobility of T À3/2 varies approximately between 120 and 300 K. But, the mobility values are low by approximately one order in comparison with our values [18]. They explained that the cause of the low values of the Hall mobility might be due to an electrical compensation by the native defects or the extrinsic impurities, because Si acts a donor when it replaces the Al site.…”
Section: Temperature Dependence Of Mobility and Lowtemperature Photolsupporting
confidence: 93%
See 2 more Smart Citations
“…This is coincided with the mobility result obtained by Chichibu et al [18]. For the CuAlSe 2 bulk grown by iodine chemical vapor transport, they reported that the mobility of T À3/2 varies approximately between 120 and 300 K. But, the mobility values are low by approximately one order in comparison with our values [18]. They explained that the cause of the low values of the Hall mobility might be due to an electrical compensation by the native defects or the extrinsic impurities, because Si acts a donor when it replaces the Al site.…”
Section: Temperature Dependence Of Mobility and Lowtemperature Photolsupporting
confidence: 93%
“…This indicates that scattering at the high-temperature range is mainly due to the acoustic mode of lattice vibration through a deformation potential and scattering at low-temperature range is most pronounced due to the impurity effect [17]. This is coincided with the mobility result obtained by Chichibu et al [18]. For the CuAlSe 2 bulk grown by iodine chemical vapor transport, they reported that the mobility of T À3/2 varies approximately between 120 and 300 K. But, the mobility values are low by approximately one order in comparison with our values [18].…”
Section: Temperature Dependence Of Mobility and Lowtemperature Photolsupporting
confidence: 79%
See 1 more Smart Citation
“…CuAlX 2 (X = S, Se, Te) belongs to the family of chalcopyrites, in experiments several studies have been carried [15,16] on the electronic, electrical, and optical properties of CuAlX 2 (X = S, Se, Te) at ambient pressures. However, high-pressure studies of these chalcopyrite semiconductors have attracted considerable attention due to their phase transition and electronic properties [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that while chalcopyrite with band gap between 1 and 1.4 eV such as CIS and CIGS can exhibit either n-or p-type conductivity by varying their composition [2], it is far more difficult to achieve n-type chalcopyrite with broader band gap such as CGS and CuAlSe 2 [12][13][14]. To our knowledge, up to now, no information is available in the case of small band gap chalcopyrite thin films.…”
Section: Introductionmentioning
confidence: 99%